2019
DOI: 10.1177/1010539519865053
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Illicit Drug Use Among Malaysian Male Adolescents

Abstract: This study was carried out to determine the prevalence of illicit drug use and its associated factors among male adolescents in Malaysia. Data of 13 135 adolescents were extracted from the National Health and Morbidity Survey 2017, a cross-sectional survey among school-going adolescents in Malaysia aged between 13 and 17 years, using a 2-stage stratified cluster sampling. A complex sample design analysis and multiple logistic regression analysis were applied. The overall prevalence of lifetime illicit drug use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
1
7
1
Order By: Relevance
“…The pattern of illicit drug use among Indonesian students was different from previous studies that found a higher prevalence of illicit drug use among older participants (Rudatsikira et al, 2009;Sirirassamee & Sirirassamee, 2015;Swendsen et al, 2012;Tsitsimpikou et al, 2018;Vidourek et al, 2018). However, this pattern also differed from another study that found a higher prevalence of illicit drug use among younger participants (Rodzlan Hasani et al, 2019). This finding was probably due to the strong effect of peer influence during middle adolescence.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…The pattern of illicit drug use among Indonesian students was different from previous studies that found a higher prevalence of illicit drug use among older participants (Rudatsikira et al, 2009;Sirirassamee & Sirirassamee, 2015;Swendsen et al, 2012;Tsitsimpikou et al, 2018;Vidourek et al, 2018). However, this pattern also differed from another study that found a higher prevalence of illicit drug use among younger participants (Rodzlan Hasani et al, 2019). This finding was probably due to the strong effect of peer influence during middle adolescence.…”
Section: Discussioncontrasting
confidence: 78%
“…The internal factors were sex and health-risk behaviors, namely, smoking, consuming alcohol, and premarital sex. A previous study among Malaysian male adolescents revealed that smoking and engaging in sexual intercourse were positively associated with lifetime drug use; they were as likely to engage in lifetime drug use (Rodzlan Hasani et al, 2019). Another study also showed that early tobacco initiation and alcohol consumption were associated with an increased likelihood of illicit drug use among older adolescents (Nkansah-Amankra & Minelli, 2016).…”
Section: Discussionmentioning
confidence: 90%
“…Other than socio-economic and physical environment factors, previous literature also reported other significant factors that contributed to substance use, such as unsupportive family condition, patient-child relationship, and being raised by a single parent [17,18]. Other factors, such as loneliness, had no close friends, inadequate peer support, involved in truancy, and being bullied, can also render adolescents vulnerable to substance use [19].…”
Section: Introductionmentioning
confidence: 99%
“…It also participates in the WHO ADR monitoring program and offers ADR information to doctors, pharmacists, and other healthcare providers. Malaysia’s present medication safety system has limitations ( Rodzlan Hasani et al, 2019 ), namely, (1) in terms of pharmaceutical vigilance, there is a lack of understanding concerning medication safety among healthcare workers, (2) there is a lack of understanding regarding the presence, function, and purpose of national ADR reporting ( Shafie et al, 2019 ), (3) due to the lack of a national computerized database on the prescription administered, signal production is difficult, (4) inability to engage pharmaceutical companies with drug safety issues, (5) there is a lack of knowledge on genetic effects, social behaviors, pharmacological interactions, and contraindications linked with medicines, (6) only a few reports on traditional and herbal medications, which are commonly utilized, are present, (7) underreporting is a key flaw in all spontaneous reporting systems, (8) nursing personnel and customers were not involved in the ADR monitoring program, (9) the role of nongovernmental organizations (NGOs) in drug safety problems is limited, (10) the function of the media in public drug safety education is limited, (11) healthcare practitioners’ selective reporting (reporting bias), and (12) inadequate at spotting delayed ADRs. These limitations play a vital role in the success or failure of the policies related to the prevention and control of drugs in Malaysia.…”
Section: Introductionmentioning
confidence: 99%